Solder joints morphology study on stacked die - Lee, Yi Xuan. (2011)
The shift from two dimensional (2D) technology to 3D packaging technology is seen as the only way to incorporate high performance into device miniaturization. Solder joint morphology has become the main reliability concern in the 3D interconnect system which is complicated by the implementation of 3D packaging with Through Silicon Vias (TSV). Therefore, this project objective is to study the relationship between the kinetics and formation of Intermetallic Compounds (IMCs) in solder bumps, and understand the growth behaviour of IMCs on stacked die at different thermal cycle regime. Design of Experiment (DOE) has been experimentally studied to optimize ion beam milling parameters to reveal the finest details in the examination of solder bumps through various characterization techniques. The experiments have successfully enhanced the electron images to a sub-micrometer scale, and results on TCJ1K readpoint (after 1000 thermal cycles) have shown that it can determine and predict the possibility of failure on a particular solder bump. Despite a localised stress concentration within C4 bump at TCJ1K, the downward trend in the overall IMCs thickness showed no sign of failure. The material integrity of the solder bump is also maintained. On the other hand, steep IMCs growth was observed at interfaces of the interposer bump. On the exclusion of the detached IMCs in the measurements, the unusual growth phenomenon observed, indicates that interposer bump has a greater risk of failure; due to its increased brittleness within the solder bump. The results concluded that C4 bump has a higher resistance to IMCs growth, which signifies a better mechanical property than the interposer bump. On a shortcoming, the stacked die results which are based on three readpoints only, may not provide a concrete evaluation on the reliability of prediction. As such, a better prediction model can be developed by increasing sample sizes with a smaller readpoint. Furthermore, by providing each solder bump with individually optimised parameters for ion milling, the accuracy of the results can be improved.